2017
DOI: 10.4103/ijo.ijo_843_16
|View full text |Cite
|
Sign up to set email alerts
|

Intra-arterial chemotherapy for retinoblastoma: Two-year results from tertiary eye-care center in India

Abstract: Aim:The aim of this study is to describe treatment outcomes and complications of selective intra-arterial chemotherapy (IAC) for intraocular retinoblastoma (RB).Materials and Methods:A retrospective, interventional series of 10 eyes with RB which underwent IAC using melphalan (5 mg/7.5 mg) and topotecan (1 mg), or melphalan (5 mg/7.5 mg) alone. Treatment outcomes were evaluated in terms of tumor control, vitreous seeds (VS) and subretinal seeds (SRS) control, and globe salvage rates.Results:Ten eyes of 10 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 14 publications
0
14
0
1
Order By: Relevance
“…Various studies have published the outcome of IAC in terms of eye salvage, recurrence, metastasis, and death. However, the choice of drugs, dosage, and techniques vary widely[122324254243444546474849505152535455565758596061] [Table 3]. Lack of prospective randomized clinical trials is a challenge in evaluating the efficacy.…”
Section: Treatment Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies have published the outcome of IAC in terms of eye salvage, recurrence, metastasis, and death. However, the choice of drugs, dosage, and techniques vary widely[122324254243444546474849505152535455565758596061] [Table 3]. Lack of prospective randomized clinical trials is a challenge in evaluating the efficacy.…”
Section: Treatment Outcomesmentioning
confidence: 99%
“…Shields et al reported a case of optic neuropathy, and three cases of optic atrophy are reported. [255157] The procedure carries the risk of permanent vision-threatening complications. Associated ischemic and occlusive chorioretinopathy, central retinal artery occlusion, vitreous hemorrhage, and retinal detachment remain a major concern when vision salvage is one of the major goals of procedure.…”
Section: Treatment Complicationsmentioning
confidence: 99%
“…Thermotherapy and cryotherapy were used as adjunctive treatments in both groups if needed. As reported previously, a limitation of IAC is that it could not always control vitreous seeding, 28 as also seen in this study. 4 The main reason for enucleation in this study was unresponsiveness of the main tumor to treatment and 76% of those unresponsive cases were patients with vitreous seeds.…”
Section: Discussionmentioning
confidence: 51%
“…[ 24 ] In yet another study on 10 eyes with active retinoblastoma who received a mean of 3.8 intra-arterial injection of topotecan and melphalan, the authors found complete regression of the main tumor in 90% and partial regression in 10% of the patients. [ 25 ]…”
Section: Discussionmentioning
confidence: 99%